Peran Struktur Pengendalian Internal Sebagai Variabel Moderasi Terhadap Faktor-Faktor Yang Mempengaruhi Keberhasilan Penerapan Enterprise Resource Planning - Dwi Nurvita; Aris Eddy Sarwono (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
This study analyzes the influence of Accounting Information Systems, human resource competence, and budget implementation on the success of Enterprise Resource Planning (ERP) implementation, with internal control structure as a moderating variable. Successful ERP implementation is essential for improving operational efficiency, enhancing the quality of accounting information, and supporting managerial decision-making. The study is motivated by the increasing demand for integrated information systems in organizations, where success depends not only on technology but also on organizational readiness, including competent human resources, adequate budgeting, and effective internal controls. A quantitative research design was employed using primary data collected through questionnaires distributed to 93 employees who actively use ERP systems in their daily work. Proportional random sampling was applied. Data were analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, coefficient of determination, and Moderated Regression Analysis (MRA). The results show that human resource competence and budget implementation have a positive and significant effect on ERP implementation success, while Accounting Information Systems do not have a significant direct effect. Simultaneously, all independent variables significantly influence ERP success, with an Adjusted R Square value of 0.691. Moderation analysis indicates that internal control structure strengthens the relationship between human resource competence and ERP success, weakens the effect of budget implementation, and does not moderate the relationship between Accounting Information Systems and ERP implementation success.